Chronic spontaneous urticaria in autoimmune connective tissue diseases - Argobi, Yahya (Journal of Pakistan Association of Dermatologists, 2022)
Objective Chronic spontaneous urticaria is one of the most troubling symptoms in autoimmune connective tissue diseases (ACTDs). Our aim is to better characterize the association between chronic spontaneous urticaria and ACTDs. Methods A retrospective study of patients seen at ACTDs clinic at Massachusetts General Hospital. Results Of the 41 patients who fit our criteria, 58% had no underlying ACTDs, 22% had systemic lupus erythematosus (SLE), and only 4% had other types of ACTDs. Conclusion Chronic spontaneous urticaria is a frequent condition in SLE. We did not find a strong association between other ACTDs and chronic spontaneous urticaria.